(untitled) (Eureka Journal of Health Sciences & Medical Innovation, 2026)
Anemia is a common hematological disorder among pregnant women, posing significant risks to both maternal and fetal health. During pregnancy, increased iron requirements, nutritional deficiencies, and chronic medical conditions can lead to reduced hemoglobin levels, resulting in maternal fatigue, weakness, and increased vulnerability to infections. For the fetus, anemia may cause intrauterine growth restriction, preterm birth, low birth weight, and perinatal mortality. This article provides an overview of the etiology, risk factors, clinical manifestations, diagnostic methods, and management strategies for anemia in pregnancy. Early detection, proper nutritional support, iron supplementation, and appropriate medical interventions are crucial for preventing adverse outcomes and ensuring the health of both mother and child.